Increased Risk of Cutaneous Squamous Cell Carcinoma in Organ Transplant Recipients and Patients on Chronic Dialysis: A Cancer Registry-based Study in Taiwan - Chao-Hsiun Tang; Yuh-Mou Sue; Wen-Ting Hsieh; Ya-Hui Wang; Chia-Chen Wang (Medical Journals Sweden, 2019)
This study investigated the predominant skin cancer subtype among organ transplant recipients, patients on chronic dialysis, and patients with chronic kidney disease in Asian subjects. Among 23,644 patients with skin cancer, identified from Taiwan Cancer Registry Database, 53 were organ transplant recipients, 255 were on chronic dialysis, 1,792 had chronic kidney disease, and 21,544 were in the control group. The proportions of squamous cell carcinoma were 52.8%, 47.8%, 40.1%, and 33.5%, respectively. Compared with the control group, organ transplant recipients (1.99-fold) and patients on chronic dialysis (1.25-fold) were at higher risk of developing squamous cell carcinoma than other skin cancers after adjustment for potential confounders. Subgroups or covariates associated with increased squamous cell carcinoma compared with other skin cancer risk included patients with chronic kidney disease aged < 70 years (vs. control group; 1.3-fold), old age (vs. young age; 2.8-fold), male sex (vs. female sex; 1.1-fold), and south Taiwan residency (vs. north Taiwan residency; 1.1-fold). Organ transplant recipients and patients on chronic dialysis had immune dysregulation, resulting in a higher risk of squamous cell carcinomas.